FRAMED BY FREEDOM: Emancipation and Oppression in Post‐Fordist Thailand. (February 2017) - SOPRANZETTI, CLAUDIO
ABSTRACT: Based on ethnographic research conducted between 2009 and 2014, this article examines the discourse of freedom ( 'itsaraphāp ) among motorcycle taxi drivers in Bangkok and the practices, both emancipatory and oppressive, that it supports and makes possible. I explore its central role in their self‐construction as successful migrants, entrepreneurial subjects, and autonomous urban dwellers, as well as its relations to capitalist restructuring and precarity in post‐crisis Thailand. I show how freedom offers a way for precarious workers—such as the drivers—to consciously make sense of and make do with political‐economic, social, and conceptual shifts taking place around them. In this sense, this article explores the construction of consent in contemporary Thailand without falling in the trap of assigning false consciousness to the drivers or of framing them as subjugated subjects. Rather, I locate the effectiveness of 'itsaraphāp discourse precisely in its ability to connect preexisting forms of exploitation, personal desires, and aspirations with a restructuring of the relations between capital and labor in contemporary Bangkok.